Muscular fitness, fatness and inflammatory biomarkers in adolescents. Issue 5 (5th July 2013) - Artero, E. G.; España‐Romero, V.; Jiménez‐Pavón, D.; Martinez‐Gómez, D.; Warnberg, J.; Gómez‐Martínez, S.; González‐Gross, M.; Vanhelst, J.; Kafatos, A.; Molnar, D.; De Henauw, S.; Moreno, L. A.; et al.
Summary What is already known about this subject Metabolic and cardiovascular diseases involve an inflammatory process that begins early in life. Muscular fitness has been inversely associated with cardiometabolic risk factors in adolescents, including inflammatory biomarkers. More research is needed to evaluate whether the influence of muscular fitness on chronic inflammation is independent of cardiorespiratory fitness and fatness. What this study adds Muscular fitness is inversely related with inflammatory biomarkers during adolescence, independently of cardiorespiratory fitness and insulin resistance. The lower inflammatory status in adolescents with higher levels of muscular fitness seems to be explained by lower levels of fatness. Overweight and obese adolescents present an exacerbated inflammatory status, but this may be counteracted – to some extent – by maintaining appropriate levels of muscular fitness. Background Muscular fitness, cardiorespiratory fitness (CRF) and fatness are mutually related with chronic inflammation. Purpose To examine the independent association of muscular fitness with inflammatory biomarkers in adolescents from nine European countries. Methods A total of 639 adolescents (296 boys) aged from 12.5 to 17.5 year were included in this report. Data collection took place in 2006–2007 and analyses in 2012. A muscular fitness score was computed from handgrip strength and standing long jump. CRF was measured using the 20 m shuttle run test. Z‐scores of C‐reactive protein, complement factors C3 and C4, leptin and white blood cell counts were summed to create a cluster of inflammatory biomarkers. Sex, age, pubertal stage and centre were used as main confounders. Additional models were further adjusted for insulin resistance (HOMA‐IR) and sum of four skinfolds. Results Muscular fitness was negatively associated with single and clustered inflammatory biomarkers (standardized β from −0.399 to −0.100, all P‐values < 0.05). Additional adjustments for CRF and HOMA‐IR weakened the associations, but they still remained significant. The association was no longer significant when adjusting for skinfolds. Decreasing values of inflammatory score were observed across incremental levels of muscular fitness in both non‐overweight and overweight adolescents (P ≤ 0.05). Conclusions Adolescents with higher levels of muscular fitness present a lower chronic inflammation, and this seems to be explained by lower levels of fatness. Yet, overweight and obese adolescents may exhibit a less adverse profile if they maintain appropriate levels of muscular fitness.